Exchanging humpty dumpties is not a solution: Why a representational view of knowledge must be replaced with an action-based approach. (19th November 2021) - Carpendale, Jeremy I. M.; Lewis, Charlie
Abstract: In arguing for knowledge representation before belief, Phillips et al. presuppose a representational theory of knowledge, a view that has been extensively criticized. As an alternative, we propose an action-based approach to knowledge, conceptualized in terms of skill. We outline the implications of this approach for children's developing social understanding, beginning with sensorimotor interaction and extending to the verbal level.